CHARACTERIZATION AND ELECTROCHEMICAL BEHAVIOUR OF BORON DOPED DIAMOND IN DETECTING AMODIAQUINE - Dewanto, Hizkia Alpha; Awali, Jatmoko; Hizam, Fadli; Destiny, Keysi Devain; Al Habib, Irsyad; Nabila, Najwa; Handayani, Murni; Triana, Yunita (Indonesian Physical Review, 2024)
Amodiaquine (AQ) is an essential medicine in treating malaria. Yet, the threat of drug resistance and toxicity necessitates accurate measurement of AQ in the human body. This research determines the amodiaquine (AQ) detection performance of boron-doped diamond (BDD) working electrodes. The study utilizes different pulse velocity (DPV) methods to analyze the AQ reaction behavior of BDD. The research demonstrates the reaction mechanism: Two electrons are transferred, and irreversible oxidation reactions occur. The sensor limit of detection (LOD) is measured to determine the performance of working electrodes for AQ detection. The LOD is calculated between 0.0645 µM and 0.3 µM, and changes in analytical concentrations relative to maximum current are calculated. The LOD of the BDD electrode is 1.5×10–8 M, lower than previous research on AQ sensors, showing the effectivity of the BDD electrode as an AQ sensor.